Tpc1 is an important Zn(II)2Cys6 transcriptional regulator required for polarized growth and virulence in the rice blast fungus. - Rita Galhano; Adriana Illana; Lauren S Ryder; Julio Rodríguez-Romero; Marie Demuez; Muhammad Badaruddin; Ana Lilia Martinez-Rocha; Darren M Soanes; David J Studholme; Nicholas J Talbot; Ane Sesma (PLoS Pathogens)
The establishment of polarity is a critical process in pathogenic fungi, mediating infection-related morphogenesis and host tissue invasion. Here, we report the identification of TPC1 (Transcription factor for Polarity Control 1), which regulates invasive polarized growth in the rice blast fungus Magnaporthe oryzae. TPC1 encodes a putative transcription factor of the fungal Zn(II)2Cys6 family, exclusive to filamentous fungi. Tpc1-deficient mutants show severe defects in conidiogenesis, infection-associated autophagy, glycogen and lipid metabolism, and plant tissue colonisation. By tracking actin-binding proteins, septin-5 and autophagosome components, we show that Tpc1 regulates cytoskeletal dynamics and infection-associated autophagy during appressorium-mediated plant penetration. We found that Tpc1 interacts with Mst12 and modulates its DNA-binding activity, while Tpc1 nuclear localisation also depends on the MAP kinase Pmk1, consistent with the involvement of Tpc1 in this signalling pathway, which is critical for appressorium development. Importantly, Tpc1 directly regulates NOXD expression, the p22phox subunit of the fungal NADPH oxidase complex via an interaction with Mst12. Tpc1 therefore controls spatial and temporal regulation of cortical F-actin through regulation of the NADPH oxidase complex during appressorium re-polarisation. Consequently, Tpc1 is a core developmental regulator in filamentous fungi, linking the regulated synthesis of reactive oxygen species and the Pmk1 pathway, with polarity control during host invasion.